Analysis on Teaching Online Strategy in Speaking Skill Used a Teacher in School: Analisis Strategi Pengajaran Online dalam Keterampilan Berbicara yang Digunakan Guru di Sekolah - Intania Dwiyanti Riduawan; Dian Rahma Santoso (Universitas Muhammadiyah Sidoarjo, 2022)
Teaching strategy is a sequence of activities that systematic, general patterns of teacher activities that include about the sequence of learning activities, the order of achieving the goals that have been specified.The objective of the research are: (1) to identify the strategies used by the English teacher in teaching speaking . (2) To find out the problems faced by the English teacher in teaching strategy on speaking .The research methodology in this research is a descriptive-qualitative design. The subject of the research is the teacher of class at the seventh grade of Junior High School, in here only one teacher and the students it is consist of 31 students that one class only.the strategies in teaching speaking that are: use the Individual work, based on activities on easy language, give instruction or training in discussion skills, and keep students to speak the target language. The techniques of collecting the data in this research are: doing interview with English teacher. This technique of data analysis which used in this research was interactive model of analysis, the model of data analysis from Miles and Huberman. That are: colleting the data, reducing the data, presenting the data and drawing conclusion. In this study used data triangulation, source and theory. This research finding that the teaching strategies used the teacher in speaking class of full day class at seventh grade in SMP Hangtuah 5 Candi . The first meeting, the teacher in teaching speaking skill used three strategies that are: used keep students to speak the target language, base the activities on easy language, and the teacher used the Individual work.